Faktor-Faktor Yang Mempengaruhi Sikap Stigma Terhadap HIV/AIDS Pada Mahasiswi Kesehatan Di Kota Bogor - Annisa Fitri Rahmadini; Imas Nurjanah; Nurul Azmi; Fikria Nur Ramadani (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
HIV stigma is negative attitudes and beliefs about HIV sufferers. One of the obstacles in controlling HIV/AIDS is stigma and discrimination against People living with HIV/AIDS (PLWHA). Stigma and discrimination are carried out by ordinary people, including students who do not have sufficient knowledge about HIV/AIDS. This research aims to determine the factors that influence stigmatizing attitudes towards HIV/AIDS among health students in Bogor. This research activity was carried out at the Prima Husada Bogor Midwifery Academy. The method used is quantitative analysis with a descriptive correlation research design with a cross sectional approach. Using an incidental sampling technique with an online questionnaire measuring tool consisting of 38 questions, there were 180 respondents from the total sampling results. Data were analyzed using the Chi-Square test with a confidence level of 95%. Results: Based on the research results, 60.6% of students have stigmatized attitudes, 82.2% of students have marital status of parents who live together, 53.9% of people have less knowledge about HIV/AIDS, 53.3% of people lack sources of information, 60 .6% have less trust, 48.3% of people have a negative attitude towards HIV/AIDS, and 72.8% live in rural areas. There is a strong correlation in the level of knowledge and stigma with p-value = 0.000. and p-value 0.003, and there is a significant correlation between attitudes and stigma, with p-value 0.037. The result is that stigmatization of attitudes among young women is influenced by factors of knowledge, belief and attitudes towards HIV/AIDS and PLWHA.